Titanic : disaster at sea - Callery, Sean. (New York : Scholastic Inc., 2013)
Describes the 1912 sinking of the "R.M.S. Titanic" and the efforts that have been made to recover the wreckage and understand why the "unsinkable" ship sank.
Includes index.
3.9
K-3
Keywords: Titanic (Steamship) -- History -- Juvenile literature; Titanic (Steamship) -- History; Titanic (Steamship) -- History; Readers (Elementary)